Nyanja/Chewa Proverbs as Didactics: Recontextualising Indigenous Knowledge for Academic Writing. (1st December 2016) - Banda, Felix; Banda, Dennis
Abstract: The paper explores how Nyanja/Chewa proverbs as stores of indigenous knowledge can be used to teach Nyanja/Chewa morphology and grammar, and as a tool to sensitise learners on aspects of academic writing. Using systemic functional linguistics and selected Nyanja/Chewa proverbs, the researchers illustrate how the patterning and the realisation of proverbs as texts in social contexts scaffold interpersonal meanings including appraisal and attitude, and stance. In turn, the researchers argue that proverbs typically have two thematically related parts, which can be used to teach aspects of academic writing in respect to appreciation of textual cohesion and coherence in meaning making. The researchers show that proverbs are typically structured to express evidentially, absolute truth and flawless logic, all of which are characteristic of academic writing. The researchers conclude that proverbs can be used as resources in the teaching aspects of persuasive language and, critical and cognitively demanding analytical skills.